The bad seed - John, Jory; Oswald, Pete (New York : Harper, 2017)
A bad seed who cuts in line, never washes his hands or feet, and lies.
School Library Journal starred, June 2017
Publisher's Weekly, May 2017
Booklist, August 2017
Kirkus Review, May 2017
2.0
K-3
Keywords: Seeds -- Fiction; Behavior -- Fiction; Seeds -- Fiction; Humorous fiction; Humorous fiction; Conduct of life -- Juvenile fiction